Modeling of the optimal fleet structure and perspective directions of its work - Вишневский, Дмитрий Олегович (Technology audit and production reserves, 2015)
In this research it is consider the structure optimization problem of the fleet structure and areas of its work within the annual period of time. It is analyzed the disadvantages in the existing approaches to solving this problem. Based on the requirements of practice and specificity of the annual planning period the main requirements to the fleet structure, on their basis are formulated and an economic-mathematical model on their base is developed. The model takes into account the fact that the fleet structure within the annual period of time can vary by chartering / chartering out of ships. The result of the model implementation is the optimal combination of "set of ships" - "set of freight traffic", providing a maximum profit in the period under review. In this case the main limitation is demand. The criterion for optimizing the fleet structure and directions of its work is profit, which takes into account the potential downtime of ships and related loss of revenue and operating expenses. The presented model can be used in the practice of maritime carriers to address issues on freight policy and marketing policy.